Evaporation From Unsaturated Soils as a Function of the Air and Soil Sides of the Land Surface. Issue 12 (23rd December 2020) - de Amesti, Pedro; de la Fuente, Alberto; Suárez, Francisco
Abstract: A theoretical framework for computing the evaporation from unsaturated soils is presented and validated based on laboratory experiments that were conducted in an uncontrolled environment where forcing variables vary in time according to diurnal meteorological cycles. This theory introduces a dimensionless number that controls the ratio between the actual and potential evaporation from unsaturated soils. The dimensionless number depends on the transfer velocity, which characterizes evaporation into the atmosphere, the diffusion coefficient of water vapor in the soil, and the water table depth. We show that depending on the value of the dimensionless number, evaporation can be limited by either the air‐side or the soil‐side of the land surface. For large transfer velocity values, evaporation is controlled by water vapor diffusion in the soil, while for shallow water tables, evaporation is controlled by water vapor transport from the land surface into the atmosphere. Despite the good agreement between the shape of the observed and predicted evaporation rates, a fitted dimensionless parameter is required to match the predicted evaporation rates. Possible explanations for this disagreement are given in the discussion. Plain Language Summary: This article seeks to understand and quantify the hydrological cycle in closed basins that are found in the Altiplano region of the Andes Cordillera of South America. These closed basins are found in the desert and, by definition, have no outflow rivers, so the water that precipitates in the catchment must be completely evaporated within the catchment. An important part of this evaporation occurs in the open wetlands (many of which are protected by both national and international laws), which are found in the central depression of the basin, as well as in from the surrounding desert, where groundwater is located at a certain depth below the land surface. In this article, we propose and validate a simple expression for computing soil water evaporation and conduct laboratory experiments in an uncontrolled environment where air and soil temperatures, air humidity, and wind speed vary over time according to diurnal meteorological cycles. Key Points: A theoretical framework is presented that introduces a dimensionless number for computing the evaporation from unsaturated soils Evaporation can be limited by either air or the soil side of the land surface depending on the value of dimensionless number Laboratory experiments in an uncontrolled environment were used to validate the theoretical framework